Poligami Dalam Perspektif Hukum Islam: Analisis Syarat dan Implementasinya - Muaidi (STIS DAFA MATARAM, 2025)
Polygamy is one of the Islamic laws (sharia) revealed by Allah SWT for the Muslim community with specific wisdom and blessings. This study aims to analyze the law of polygamy in Islam, the requirements that must be fulfilled, and its implementation in the context of modern life. The method used is library research with a descriptive-analytical approach to primary and secondary Islamic legal sources. The research results show that the law of polygamy is fundamentally permissible (mubah) but is not a recommendation, with strict conditions including the ability to act justly toward all wives, the ability to provide material and spiritual sustenance, permission from the first wife according to some scholars, and emergency conditions that necessitate it. The implementation of polygamy must consider aspects of justice, welfare (maslahah), and must not cause harm (mudarat) to the family.